Effects of formative testing on junior secondary school students' achievement in integrated science (2010)
This study examined the effect of formative testing on students' achievement in integrated science. The study adopted a 4x2 factorial design with pre-test and post-test control groups in quasi-experimental setting. Treatment was administered at four levels: (teaching, formative testing, feedback and remediation; teaching, formative testing, no feedback and no remediation; teaching, formative testing, no feedback and no remediation; teaching, no formative testing, no feedback and and no remediation(control group). The moderator variable was parental involvement at two levels (male and female). One hundred and twenty nine junior secondary school two (J. S.2) studetns from eight selected secondfary schools from Ibadan North Local government area of Oyo state participated in the study. Three instruments were used: two response instruments-integrated sceince achievement test (ISAT) and formative test and one stimulus instrument (teaching package). The data analysis was done using Analysis of Covariance (ANCOVA) witht he pre-test score serving as covariates. The results indicated that there is a significant main effect of treatment F(3,119)=89.68;P<0.05) on students' achievement in integratedscience, parental involvement was recorded. The implications of this study include the use of formative testing, feedback and remediation to complement teaching.